Motion Resistance Ratio, Net Traction Ratio and Tractive Efficiency of a Riceland Type Tyre - Khidir, Elwaleed Awad (1999)
A study was conducted to determine the accuracy of Wismer-Luth and Brixius equations in predicting the tyre motion resistance ratio, net traction ratio and tractive efficiency of a Riceland type tyre. The tyre was tested on a sandy clay loam soil in an indoor UPM tyre traction testing facility. The experiment was conducted by running the tyre in two modes; towing mode for the formulation of tyre motion resistance ratio equation and driving mode for the formulation of tyre net traction ratio and tractive efficiency equations. A total of ninety test runs were involved in the tyre motion resistance ratio determinations at three selected inflation pressures (i. e. 221, 193 and 166 kPa) and selected wheel numerics ranging between 0 to 70. From the analysis of covariance (ANCOVA) it was found that both inflation pressure and wheel numeric has significant effect on the tyre motion resistance ratio. Regression analysis was also conducted to determine the closeness offit for Wismer-Luth and Brixius equations in predicting the motion resistance ratio of the tested tyre. Finally, 3 new logarithmic models for the tyre motion resistance ratio were formulated. The 193 kPa inflation pressure revealed a lower tyre motion resistance than the nominated pressure (i.e. 221 kPa) and the 166 kPa. For the tyre net traction ratio and tractive efficiency determinations, 126 test runs were conducted in a combination consisting of three selected inflation pressures (i.e. 221 , 193 and 166 kPa) and two wheel numerics (i.e. 19 and 29) representing two extreme types of soil strength under different levels of travel reduction ranging between 0 to 40%. Regression analysis was conducted to determine the prediction equation describing the tyre torque ratio. Marqurdt' s method used by Wismer-Luth for predicting non-linear equation was found not suitable in predicting the torque ratio of the tested tyre for its low coefficient of determination and inadequacy. The logarithmic model was found to be suitable in predicting the torque ratio. From the analysis of covariance (ANCOVA) the mean effect of travel reduction, tyre inflation pressure and wheel numeric were found to be highly significant where as the interaction of inflation pressure and wheel numeric was not significant. The 193 kPa inflation pressure was the best, among the three inflation pressures used, in getting higher net traction ratio and higher maximum tractive efficiency.